Social Assistance Transfers in Bosnia and Herzegovina : Moving Toward a More Sustainable and Better-Targeted Safety Net - World Bank (Washington, DC, 2014)
Public expenditures on non-insurance social protection cash transfers absorb a huge share of the entities' respective budgets. This level of spending requires buoyant public revenues. However, public revenues will be under continuing pressure in view of the impending economic crisis. Moreover, devoting a large proportion of public funds to social transfers has the effect of crowding out resources that could be devoted to public investments which will be increasingly needed to stimulate growth as the economy begins to sag under the impact of the world economic crisis. In addition, there is evidence that some rights based programs create disincentives for employment. This situation is fiscally unsustainable, economically inefficient, and socially inequitable. Bosnia and Herzegovina (BH) needs to completely overhaul it s non-insurance social protection cash transfer programs. There are many ways in which BH could reform these programs and put in place measures aimed at developing a social safety net that is: (a) less of a burden on public resources, (b) more efficient, and (c) better targeted to the poor. Specifically, it is recommended that the governments in BH consider a three pronged approach with measures to: 1) improve and introduce targeting mechanisms to better channel resources to the poor; 2) strengthen benefits administration and beneficiary registry systems; and, 3) rationalize disability-related benefit schemes. An increasingly widespread recognition of the need for rationalization of the non-insurance social protection cash benefits is discernible in both the decision-making circles and in the public discourse in BH.